2019
DOI: 10.1136/jnnp-2019-321758
|View full text |Cite
|
Sign up to set email alerts
|

Long-term deep brain stimulation of the ventral anterior limb of the internal capsule for treatment-resistant depression

Abstract: ObjectiveDeep brain stimulation (DBS) reduces depressive symptoms in approximately 40%–60% of patients with treatment-resistant depression (TRD), but data on long-term efficacy and safety are scarce. Our objective was to assess the efficacy and safety of DBS targeted at the ventral anterior limb of the internal capsule (vALIC) in 25 patients with TRD during a 1-year, open-label, maintenance period, which followed a 1-year optimisation period.MethodsDepression severity was measured using the 17-item Hamilton De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 31 publications
1
56
0
1
Order By: Relevance
“…Another important factor in trial design is the length of time that the patient undergoes therapy. Long-term open-label studies have demonstrated that the efficacy of DBS for TRD improves over time, so longer trials may be necessary [17,18,38,66,67]. Finally, depression severity waxes and wanes throughout a patient's disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor in trial design is the length of time that the patient undergoes therapy. Long-term open-label studies have demonstrated that the efficacy of DBS for TRD improves over time, so longer trials may be necessary [17,18,38,66,67]. Finally, depression severity waxes and wanes throughout a patient's disease course.…”
Section: Discussionmentioning
confidence: 99%
“…This event demonstrates that the sudden discontinuation of stimulation can result in a recurrence of depressive symptoms. The results of DBS therapy are satisfactory, which enables further support in research into this method of treatment for patients with drug-resistant depression [21].…”
Section: Affective Disordersmentioning
confidence: 76%
“…The study's primary outcome was a comparison between depression scores in the ON and OFF groups, which showed significantly better depression scores during active rather than sham stimulation. The overall response rate during the 12 months open-label phase was 10/25 (40%), and twoyear follow up data were recently published, with 8/25 (32%) meeting responder status [10]. This was the first example that DBS for TRD may require an adaptive trial design, with a prolonged optimization period to establish optimal stimulation settings and extinguish placebo responses.…”
Section: Expert Commentarymentioning
confidence: 81%